Endoscopic Retrieval of Cloth (Foreign Body) from the Stomach of a Dog – A Case Report - Atmakur Venkatesh; K. Mohanambal; K.R.R. Reddy; M. Elavarasan; A. Rakki Raja; K.K. Ponnu Swamy; D. Sumathi; K. Jayakumar (The Indian Veterinary Journal, 2026)
A four-year-old male German Shepherd was presented with a history of intermittent vomiting, anorexia, and lethargy for the past two days. Abdomen palpation revealed a firm mass in the cranial abdomen. Abdominal ultrasonography identified a hyperechoic area with acoustic shadowing in the gastric region. Gastroscopy revealed cloth in the stomach, which was retrieved using an endoscopic snare. The animal showed marked improvement with resolution of clinical signs.